Evolution of humoral lesions on follow-up biopsy stratifies the risk for renal graft loss after antibody-mediated rejection treatment. Issue 12 (8th June 2022) - Bouchet, Antonin; Muller, Brieuc; Olagne, Jerome; Barba, Thomas; Joly, Mélanie; Obrecht, Augustin; Rabeyrin, Maud; Dijoud, Frédérique; Picard, Cécile; Mezaache, Sarah; Sicard, Antoine; Koenig, Alice; et al.
ABSTRACT: Background: The standard-of-care protocol, based on plasma exchanges, high-dose intravenous immunoglobulin and optimization of maintenance immunosuppression, can slow down the evolution of antibody-mediated rejection (AMR), but with high interindividual variability. Identification of a reliable predictive tool of the response to AMR treatment is a mandatory step for personalization of the follow-up strategy and to guide second-line therapies. Methods: Interrogation of the electronic databases of 2 French university hospitals (Lyon and Strasbourg) retrospectively identified 81 renal transplant recipients diagnosed with AMR without chronic lesions (cg score ≤1) at diagnosis and for whom a follow-up biopsy had been performed 3–6 months after initiation of therapy. Results: The evolution of humoral lesions on follow-up biopsy (disappearance versus persistence versus progression) correlated with the risk for allograft loss (logrank test, P  = .001). Patients with disappearance of humoral lesions had ∼80% graft survival at 10 years. The hazard ratio for graft loss in multivariate analysis was 3.91 ( P  = .04) and 5.15 ( P  = .02) for patients with persistence and progression of lesions, respectively. The non-invasive parameters classically used to follow the intensity of humoral alloimmune response (evolution of immunodominant DSA mean fluorescence intensity) and the decline of renal graft function (estimated glomerular filtration rate decrease and persistent proteinuria) showed little clinical value to predict the histological response to AMR therapy. Conclusion: We conclude that invasive monitoring of the evolution of humoral lesions by the mean of follow-up biopsy performed 3–6 months after the initiation of therapy is an interesting tool to predict long-term outcome after AMR treatment. Graphical Abstract: